Breast cancer staging in population-based registries: an alert to the quality of information - Soares, Leonardo Ribeiro; Curado, Maria Paula; Freitas-Junior, Ruffo (Mastology, 2021)
Objective: To discuss the practical difficulties associated with breast cancer staging, especially in the context of population- based cancer registries (PBCR). Methods: This is a short communication that discusses the importance and temporal evolution of breast cancer staging, as well as the limitations and new challenges associated with this process. Results: This study discusses the importance and temporal evolution of breast cancer staging, as well as the limitations and new challenges associated with this process. Minimal divergences in physical examination and disagreements in imaging tests can classify the patient in a higher or lower stage of the disease. In some population-based registries, up to 20% of the information regarding the clinical stage of breast cancer may be mistaken. Conclusion: We highlight the necessity for continuing education and constant training for all professionals involved in the breast cancer epidemiological context. The utilization of new technologies can help standardize the information and reduce the divergences related to cancer staging registry.